2017
DOI: 10.1007/s00431-017-2997-6
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic predisposition in children with cancer – affected families' acceptance of Trio-WES

Abstract: A considerable percentage of childhood cancers are due to cancer predisposition syndromes (CPS). The ratio of CPSs caused by inherited versus de novo germline mutations and the risk of recurrence in other children are unknown. We initiated a prospective study performing whole-exome sequencing (WES) of parent-child trios in children newly diagnosed with cancer. We initially aimed to determine the interest in and acceptance of trio WES among affected families and to systematically collect demographic, medical, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 21 publications
(23 reference statements)
0
43
0
2
Order By: Relevance
“…Whole-exome sequencing (WES) of peripheral bloodderived DNA of the parent-child trio was performed. Details on data analysis are given in the Supplemental material [11]. Taken together, we identified 461 inherited heterozygous sequence variations of probable consequences including missense (444), frameshift (9), inframe insertion and deletions (6), and start/stop-codons (2), occurring with an allele frequency of less than 5% (MAF ≤ 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Whole-exome sequencing (WES) of peripheral bloodderived DNA of the parent-child trio was performed. Details on data analysis are given in the Supplemental material [11]. Taken together, we identified 461 inherited heterozygous sequence variations of probable consequences including missense (444), frameshift (9), inframe insertion and deletions (6), and start/stop-codons (2), occurring with an allele frequency of less than 5% (MAF ≤ 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Research by Brozou et al demonstrated a much higher rate of uptake of ES in families of children with cancer, at 88.3%; however, this was assessed after the ES consent process. It may be that the consent process, which contains educational elements similar to those covered within a genetic counseling session, alleviated uncertainty, leading to uptake of ES . As resources permit, referral for pretest genetic evaluation and counseling is recommended to facilitate decision making regarding germline genetic testing.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these considerations, research has previously demonstrated interest in genetic testing for CPS among pediatric oncology patients and their families; however, for many, this testing is not yet routinely available at the clinic . In addition, little is known about sociodemographic factors influencing interest among this population.…”
Section: Introductionmentioning
confidence: 99%
“…WES of parent-child trios has become a widely used strategy to identify presumably pathogenetic genetic variants in children with rare diseases. However, it has not yet been routinely implemented in pediatric oncology, with few exceptions (71). Genome-wide approaches generate huge amounts of genetic data and it remains challenging to interpret the identified variants.…”
Section: Molecular Diagnostics Of Cpssmentioning
confidence: 99%